HAZARD ANALYSIS CRITICAL CONTROL POINT PADA PRODUKSI PERKEDEL DAGING DI INSTALASI GIZI RUMAH SAKIT MUHAMMADIYAH LAMONGAN - Widya Endirasari; Ponco Ali Yuswanti; Dwi Novri Supriatiningrum (Ghidza Media Jurnal, 2021)
HACCP (Hazard Analysis Critical Control Point) was quality assurance system used in supervision in hospital nutrition services. The application of HACCP at Muhammadiyah Hospital Lamongan in production at the nutrition installation was carried out to anticipate hazards and identify control points by paying attention to preventive measures rather than control in testing meat perkedel products. The research design used in this study is descriptive analytic which aims to determine the application of HACCP to the production of meat perkedel in the nutrition installation of Muhammadiyah Hospital Lamongan. Some of the HACCP implementations are not appropriate, namely the HACCP team, the requirements of the HACCP team members, quality control tasks, and APD forms. The implementation of HACCP had been in accordance with the schedule of HACCP verification on patient food processing and control devices at the nutrition installation of Muhammadiyah Hospital Lamongan.